An energy-aware cooperative content distributed strategy based on MST for the mobile environment. (2017) - Wang, Nao; Wang, Gaocai; Xie, Tianxiao
In a mobile environment, they will consume less energy if mobile terminals download the common interesting content from each other by using short-range wireless transmission technology. This paper mainly focuses on energy-aware cooperative content distribution strategy for these mobile networks. Considering the characteristics of wireless networks and energy consumption of mobile terminals, we construct an energy consumption optimisation model with energy consumption fairness constraint and then solve it by using minimum spanning tree (MST) based on a distributed algorithm. We obtain simulation results under NS-2 tool, and compare them with the minimal energy consumption scheme and the no-cooperation scheme at total energy consumption and the fairness of energy consumption. Performance analysis results show that the proposed strategy can decrease the total energy consumption significantly for mobile terminals, and obtain the balance at the energy consumption.